Differences in Rumination and Animal Activity Can Be Quantified by Utilizing New Technologies - M. A. Scilacci; A. J. Tarpoff; E. C. Titgemeyer; T. G. O'Quinn; T. Jennings; C. I. Vahl; D. U. Thomson; W. R. Hollenbeck; D. A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:Utilizing new technologies such as Allflex eSense Ear Tags to (Allflex Livestock Intelligence, Madison, WI) evaluate the impacts of limit feeding a high-energy diet in the backgrounding phase on daily rumination and activity in growing cattle. Study Description:This project was conducted in conjunction with the performance backgrounding study at the Kansas State University Beef Stocker Unit in 2019. Crossbred heifers (n = 418) were outfitted with an ear tag that measured rumination and activity throughout the day and the 84-day backgrounding study. This data was continuously collected via an onsite antenna, downloaded to a computer, and analyzed in a software program. The Bottom Line:High-energy, limit-fed cattle ruminate less than high roughage, ad libitum cattle by 45 minutes in this study. There were no detected differences in animal activity.
Keywords: limit feeding; rumination; activity